Age‐related differences in morbidity and mortality after surgery for primary clinical T4 and locally recurrent rectal cancer. (17th February 2021) - Ketelaers, S. H. J.; Voogt, E. L. K.; Simkens, G. A.; Bloemen, J. G.; Nieuwenhuijzen, G. A. P.; de Hingh, I. H. J.; Rutten, H. J. T.; Burger, J. W. A.; Orsini, R. G.
Abstract: Aim: Outcomes in elderly patients (≥75 years) with non‐advanced colorectal cancer have improved. It is unclear whether this is also true for elderly patients with clinical T4 rectal cancer (cT4RC) or locally recurrent rectal cancer (LRRC). We aimed to compare age‐related differences in morbidity and mortality after curative treatment for cT4RC and LRRC. Methods: All cT4RC and LRRC patients without distant metastasis who underwent curative surgery between 2005 and 2017 in the Catharina Hospital (Eindhoven, The Netherlands) were included. Morbidity and mortality were evaluated based on age (<75 and ≥75 years) and date of surgery (2005–2011 and 2012–2017). Results: Overall, 72 of 474 (15.2%) cT4RC and 53 of 293 (18.1%) LRRC patients were ≥75 years. No significant differences in the incidence of Clavien–Dindo I–IV complications were observed between age groups. However, in elderly cT4RC patients, cerebrovascular accidents occurred more frequently (4.2% vs. 0.5%, P = 0.03). Between 2005–2011 and 2012–2017, 30‐day mortality improved from 7.5% to 3.1% and from 10.0% to 0.0% in elderly cT4RC and LRRC patients, respectively. The 1‐year mortality during 2012–2017 was worse in elderly than in younger patients (28.1% vs. 6.2%, P = 0.001 for cT4RC and 27.3% vs. 13.8%, P = 0.06 for LRRC). In elderly cT4RC and LRRC patients, 44.4% and 46.2% died due to non‐cancer‐related causes, while only 27.8% and 23.1% died due to disease recurrence, respectively. Conclusion: Although the 30‐day mortality in elderly cT4RC and LRRC patients improved after curative treatment, the 1‐year mortality in elderly patients continued to be high, which requires more awareness for the elderly after hospitalization.